DOI: 10.18297/etd/1292
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of first-semester student attrition in a community college.

Abstract: Scott, Ophelia Turner 1953-, "An exploratory study of first-semester student attrition in a community college." (2010 The purpose of this exploratory study was to determine if student background variables (age, gender, race, academic preparation); student status (part/full-time student), and student circumstances (commuting distance, independent!dependent financial student status) could predict fall-to-spring attrition (2006)(2007) in a sample of 542 first-time, first-semester students at a community college … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…This study supported previous studies by Chambers (2007) who cited quality of placements as a major factor in student attrition, and studies by Scott (2005) who found that negative attitudes and behaviours of placement and poor mentorship impacted on student nurse attrition. Koh (2002) suggested that students who are not helped to link theory with practice through placement experiences often leave their nursing programmes.…”
Section: Placement Learningsupporting
confidence: 90%
“…This study supported previous studies by Chambers (2007) who cited quality of placements as a major factor in student attrition, and studies by Scott (2005) who found that negative attitudes and behaviours of placement and poor mentorship impacted on student nurse attrition. Koh (2002) suggested that students who are not helped to link theory with practice through placement experiences often leave their nursing programmes.…”
Section: Placement Learningsupporting
confidence: 90%
“…Some problem-focused coping strategies are examples of this type (see Lazarus, 1991, 1993). The type of coping strategies aimed at the internal environment are to enhance and protect the self or one’s cognitive models of the world (see Scott & Clark, 1999). One aspect of this is the regulation of positive and negative emotions, such as depression (Fitzsimmons & Martin, 1999).…”
Section: Evidence For a Systematic Framework For Psychotherapymentioning
confidence: 99%